Perceived school climate factors of bullying among Gweru urban high school adolescents : indicators for intervention - Ncube, Neddie (Midlands State University, 2016)
The aim of the study was to investigate on school climate factors of bullying among Gweru urban High school adolescents. A survey design, premised on quantitative and qualitative paradigms, was used. Stratified random sampling was used to select 2 of the 6 day- and 2 of the 7 day-boarding schools. Purposive sampling was used to select 1 class from each school, giving 76 female and 84 male students (mean age 16). A Questionnaire was self-administered, and for close-ended questions, median values of students’ responses were calculated, and the data was also subjected to Spearman’s rho correlational computations among the factors. Thematic analysis was used with data obtained from open-ended questions. Main findings were that students perceived factors of bullying as being comprised of a negative teaching-learning process, poor social interactions, and a negative general school tone. It was concluded that dysfunctional school climate factors promoted bullying in complex interactive ways. However, other confounding variables could explain why some students exposed to such factors, did not bully while others, not exposed, bullied. Thus, the study’s findings could only have permitted probable factors rather than undisputed ones. Recommendations made included that anti-bullying program-designers could address the factors in both their individual capacities and in combination, as changes in one could likely influence changes in others.